Resin composition
A resin composition combining polyolefin resin, hydrophilically modified polyolefin resin, and N-vinyl lactam polymer addresses dispersibility and hydrophilicity issues, improving the suitability of polyolefin resins for textiles and sanitary materials.
Patent Information
- Application Number
- JP2023104384
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-06-26
- Publication Date
- 2025-01-15
AI Technical Summary
Existing resin compositions for polyolefin resins fail to adequately disperse N-vinyl lactam polymers, leading to insufficient hydrophilicity and dispersibility, which is necessary for applications requiring hygroscopic properties in textiles and sanitary materials.
A resin composition comprising a polyolefin resin, a hydrophilically modified polyolefin resin, and an N-vinyl lactam polymer, where the hydrophilically modified polyolefin resin contains hydrophilic groups such as carboxylic anhydride, carboxyl, or sulfonic acid groups, and the N-vinyl lactam polymer has a hydrophilic modification of 100 mol% structural units, ensuring excellent dispersibility and hydrophilicity.
The composition effectively imparts hydrophilicity to polyolefin resins, enhancing dispersibility and strength of molded articles, making them suitable for textile and sanitary applications.
Smart Images

Figure 2025004597000001 
Figure 2025004597000002 
Figure 2025004597000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a resin composition. More specifically, the present invention relates to a resin composition useful for fibers and the like. [Background technology]
[0002] Polyolefin resins are excellent in moldability, rigidity, electrical insulation, etc., and are therefore widely used for the production of films, fibers, and other molded products of various shapes. For example, Patent Document 1 discloses a polyolefin and polyvinylpyrrolidone blend comprising a predetermined amount of (A) an olefin-based (co)polymer, a predetermined amount of (B) a polyvinylpyrrolidone (co)polymer, and a predetermined amount of (C) an antioxidant, with the proviso that the blend does not contain an antistatic agent and carbon black.
[0003] Furthermore, synthetic resins such as polyolefin resins are suitably used in textile products and the like, but there is a demand for them to have moisture absorbency in clothing, sanitary materials, and the like. For example, regarding a technique for imparting moisture absorption to a thermoplastic resin, Patent Document 2 discloses a thermoplastic resin composition comprising a thermoplastic resin having at least one functional group selected from the group consisting of a carboxyl group, a hydroxyl group, and an amino group, and a vinylpyrrolidone copolymer having a functional group capable of reacting with the functional group of the thermoplastic resin. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] Special Publication No. 2021-516710 [Patent Document 2] JP 2002-003731 A Summary of the Invention [Problem to be solved by the invention]
[0005] As described above, a technique for imparting moisture absorption to a thermoplastic resin using a vinylpyrrolidone copolymer has been developed, but the present inventors have found that when an N-vinyllactam polymer is applied to a polyolefin resin using the above method, the N-vinyllactam polymer does not disperse sufficiently in the resin composition and aggregates. Therefore, there is room for developing a resin composition that imparts hydrophilicity to a polyolefin resin and also has excellent dispersibility of the N-vinyllactam polymer.
[0006] The present invention has been made in consideration of the above-mentioned current situation, and has an object to provide a resin composition which imparts hydrophilicity to a polyolefin resin and also has excellent dispersibility for an N-vinyl lactam polymer. [Means for solving the problem]
[0007] The present inventors have conducted extensive research into resin compositions containing polyolefin resins and have found that by combining a hydrophilically modified polyolefin resin with an N-vinyl lactam polymer, the polyolefin resin can be made hydrophilic and the dispersibility of the N-vinyl lactam polymer can be improved. These findings led to the realization of the present invention, which successfully solved the above-mentioned problems.
[0008] The present invention includes the following resin compositions and the like. [1] A resin composition comprising an N-vinyl lactam polymer (A), a polyolefin resin (B), and a hydrophilically modified polyolefin resin (C). [2] The resin composition according to [1] above, wherein the hydrophilically modified polyolefin resin (C) has at least one hydrophilic group selected from the group consisting of a carboxylic anhydride group, a carboxyl group, a sulfonic acid group, an amino group and salts thereof, and a hydroxyl group. [3] The resin composition according to [1] or [2], wherein the N-vinyl lactam polymer (A) has a structural unit (a) derived from an N-vinyl lactam monomer (A1), and the ratio of the hydrophilic group of the hydrophilically modified polyolefin resin (C) to 100 mol % of the structural unit (a) is 0.01 to 20 mol %. [4] The resin composition according to the above [1] or [2], wherein the content of the hydrophilically modified polyolefin resin (C) is 0.1 to 80 mass % relative to 100 mass % of the polyolefin resin (B). [5] The resin composition according to the above [1] or [2], wherein the content of the N-vinyl lactam polymer (A) is 0.1 to 40 mass % relative to 100 mass % of the polyolefin resin (B). [6] The resin composition according to [1] or [2] above, wherein the polyolefin resin (B) is polypropylene. [7] The resin composition according to the above [1] or [2], wherein the polyolefin resin (B) constituting the hydrophilically modified polyolefin resin (C) is polypropylene. [8] The resin composition according to the above [1] or [2], wherein the N-vinyl lactam polymer (A) has a structure derived from a phosphorus atom-containing compound. [9] The resin composition according to the above [1] or [2], wherein the N-vinyllactam polymer (A) has a content of the structural unit (a) derived from the N-vinyllactam monomer (A1) of 50 to 100 mol % relative to 100 mol % of all structural units.
[10] The resin composition according to the above [1] or [2], wherein the hydrophilically modified polyolefin resin (C) is an acid-modified polyolefin resin, and the acid value of the acid-modified polyolefin resin is 3 to 300 mgKOH / g.
[11] A hydrophilizing agent comprising an N-vinyl lactam polymer (A), the hydrophilizing agent being used in a resin composition comprising a polyolefin resin (B) and a hydrophilically modified polyolefin resin (C).
[12] A masterbatch comprising an N-vinyllactam polymer (A), and a polyolefin resin (B) and / or a hydrophilically modified polyolefin resin (C), wherein the content of the N-vinyllactam polymer (A) is 20 to 150 mass% based on the total amount of the polyolefin resin (B) and the hydrophilically modified polyolefin resin (C).
[13] A method for producing a resin composition comprising an N-vinyl lactam polymer (A), a polyolefin resin (B), and a hydrophilically modified polyolefin resin (C), the method comprising a step (α) of mixing the N-vinyl lactam polymer (A) with the polyolefin resin (B) and / or the hydrophilically modified polyolefin resin (C), and, if either the polyolefin resin (B) or the hydrophilically modified polyolefin resin (C) is not mixed in the step (α), the method comprises a step (β) of mixing the mixture obtained in the step (α) with either the polyolefin resin (B) or the hydrophilically modified polyolefin resin (C) that was not mixed in the step (α). Effect of the Invention
[0009] The resin composition of the present invention has the above-mentioned constitution, imparts hydrophilicity to the polyolefin resin, and has excellent dispersibility of the N-vinyl lactam polymer, so that it can be suitably used for textile products and the like. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] The preferred embodiments of the present invention are specifically described below, but the present invention is not limited to the following description, and can be modified as appropriate within the scope of the present invention. In addition, a combination of two or more of the individual preferred embodiments of the present invention described below also falls within the preferred embodiments of the present invention.
[0011] <Resin composition> The resin composition of the present invention contains an N-vinyl lactam polymer (A), a polyolefin resin (B), and a hydrophilically modified polyolefin resin (C). It is believed that the inclusion of the N-vinyllactam polymer (A) in the resin composition of the present invention makes it possible to impart hydrophilicity to the polyolefin resin (B), and that the inclusion of the hydrophilically modified polyolefin resin (C) makes it possible for the hydrophilic groups in the hydrophilically modified polyolefin resin (C) to interact with the polar lactam structure in the N-vinyllactam polymer (A), thereby improving the dispersibility of the N-vinyllactam polymer (A) in the resin composition. Furthermore, since the resin composition of the present invention contains the above-mentioned components, when the resin composition is molded, the strength of the molded article is also excellent.
[0012] The content of the polyolefin resin (B) in the resin composition is not particularly limited, but is preferably 45 to 99% by mass relative to 100% by mass of the resin composition. This further improves the strength of the molded article. The content of the polyolefin resin (B) is more preferably 60 to 98% by mass, and even more preferably 70 to 95% by mass.
[0013] The content of the hydrophilically modified polyolefin resin (C) in the resin composition is not particularly limited, but is preferably 0.1 to 80 mass% relative to 100 mass% of the polyolefin resin (B). This can further improve the dispersibility of the N-vinyl lactam polymer (A) in the resin composition. The content of the hydrophilically modified polyolefin resin (C) is more preferably 0.3 to 50 mass%, even more preferably 0.5 to 30 mass%, particularly preferably 0.7 to 20 mass%, and most preferably 0.8 to 10 mass%.
[0014] The content of the N-vinyl lactam polymer (A) in the resin composition is not particularly limited, but is preferably 0.1 to 40% by mass relative to 100% by mass of the polyolefin resin (B). This allows the polyolefin resin (B) to be more sufficiently hydrophilic. The content of the N-vinyl lactam polymer (A) is more preferably 1 to 30% by mass, further preferably 3 to 25% by mass, and particularly preferably 5 to 20% by mass.
[0015] (N-vinyl lactam polymer (A)) The N-vinyl lactam polymer (A) is not particularly limited as long as it has a structural unit (a) derived from an N-vinyl lactam monomer (A1). The N-vinyl lactam monomer (A1) is not particularly limited as long as it is a monomer having an N-vinyl lactam structure, and may be, for example, a monomer represented by the following formula (1);
[0016] [ka]
[0017] (In the formula, R 1 , R 2 , R 3 , R 4 are the same or different and represent a hydrogen atom or an alkyl group having 1 to 10 carbon atoms which may have a substituent. m represents an integer of 0 to 4. n represents an integer of 1 to 3. Above R 1 ~R 4 The number of carbon atoms in the alkyl group in the formula is preferably 1 to 6, and more preferably 1 to 4. The alkyl group is further preferably a methyl group or an ethyl group, and particularly preferably a methyl group. Above R 1 ~R 4 The substituent in is not particularly limited, but examples thereof include an ethylenically unsaturated hydrocarbon group; a carboxyl group, a sulfonic acid group, and esters and salts thereof; an amino group, a hydroxyl group, and the like. R 1 ~R 3 is preferably a hydrogen atom. 4 is preferably a hydrogen atom or a methyl group, and more preferably a hydrogen atom. m is preferably an integer of 0 to 2, more preferably an integer of 0 to 1, and most preferably 0. n is preferably 1 or 2, and more preferably 1.
[0018] Examples of the compound represented by the above formula (1) include N-vinylpyrrolidone, N-vinyl-5-methylpyrrolidone, N-vinylpiperidone, N-vinylcaprolactam, 1-(2-propenyl)-2-pyrrolidone, and the like, and one or more of them can be used. As the N-vinyllactam, an unsaturated monomer having a pyrrolidone ring is preferable. More preferably, it is N-vinylpyrrolidone.
[0019] The N-vinyl lactam polymer (A) may have a structural unit (e) derived from a monomer (E) other than the N-vinyl lactam monomer (A1). The other monomer (E) is not particularly limited as long as it is a compound that can be copolymerized with the N-vinyl lactam monomer, does not have a lactam structure, and has an ethylenically unsaturated hydrocarbon group. For example, it is an unsaturated monomer having a hydrophilic group in the hydrophilically modified polyolefin resin (C) described later, (meth)acrylic acid esters such as methyl (meth)acrylate, ethyl (meth)acrylate, butyl (meth)acrylate, cyclohexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, and 2-methoxyethyl (meth)acrylate; N-monomethyl (meth)acrylate, Examples of the vinyl ethers include N-substituted (meth)acrylamides such as t)acrylamide, N-monoethyl(meth)acrylamide, and N,N-dimethyl(meth)acrylamide; vinyl aryl monomers such as styrene, indene, and vinylaniline; alkenes such as ethylene, propylene, butadiene, isobutylene, and octene; vinyl amides such as vinyl formamide, vinyl acetamide, and vinyl oxazolidone; vinyl ethylene carbonate and its derivatives; and vinyl ethers such as methyl vinyl ether, ethyl vinyl ether, and butyl vinyl ether.
[0020] In the N-vinyllactam polymer (A), the proportion of the structural unit (a) derived from the N-vinyllactam monomer (A1) is preferably 50 to 100 mol % relative to 100 mol % of all structural units, more preferably 60 to 100 mol %, still more preferably 70 to 100 mol %, still more preferably 80 to 100 mol %, particularly preferably 90 to 100 mol %, and most preferably 100 mol %.
[0021] In the N-vinyl lactam polymer (A), the proportion of structural units derived from other monomers (E) is preferably 0 to 50 mol % relative to 100 mol % of all structural units, more preferably 0 to 40 mol %, still more preferably 0 to 30 mol %, still more preferably 0 to 20 mol %, particularly preferably 0 to 10 mol %, and most preferably 0 mol %.
[0022] The N-vinyl lactam polymer (A) preferably has a structure derived from a phosphorus atom-containing compound (phosphorus atom-containing group), which further improves the heat resistance of the resin composition. When the N-vinyl lactam polymer (A) has a phosphorus atom-containing group in the molecule, decomposition of the polymer when heated can be suppressed, and the heat resistance of the resin composition can be further improved. The N-vinyl lactam polymer (A) more preferably has a phosphorus atom-containing group at the main chain end (molecular end). By polymerizing the monomer components in the presence of a chain transfer agent having a phosphorus atom, a phosphorus atom-containing group can be introduced into the main chain terminal of the polymer. The phosphorus atom-containing group contained in the N-vinyl lactam polymer (A) can be analyzed, for example, by 31 This can be achieved by P-NMR measurement, etc.
[0023] The phosphorus atom-containing group is not particularly limited as long as it is a group containing a phosphorus atom, but is preferably a reducing group. Examples of the phosphorus atom-containing group having reducing properties include a hypophosphorous acid (salt) group and a phosphorous acid (salt) group. A hypophosphorous acid (salt) group is more preferred. The above-mentioned hypophosphorous acid (salt) group means a hypophosphorous acid group or a salt thereof, and the above-mentioned phosphorous acid (salt) group means a phosphorous acid group or a salt thereof.
[0024] The weight average molecular weight of the N-vinyl lactam polymer (A) is preferably 3,000 to 500,000, more preferably 5,000 to 300,000, still more preferably 8,000 to 200,000, particularly preferably 10,000 to 100,000, and most preferably 10,000 to 50,000. When the weight average molecular weight is within the above range, the dispersibility of the N-vinyl lactam polymer (A) in the resin composition can be further improved. The weight average molecular weight of the N-vinyl lactam polymer (A) can be measured by the method described in the Examples.
[0025] The N-vinyl lactam polymer (A) preferably has a K value, as determined by the Fikentscher method, of 15 to 50. It is more preferably 20 to 40, further preferably 22 to 38, and particularly preferably 23 to 35. When the K value is within the above range, the dispersibility of the N-vinyl lactam polymer (A) in the resin composition can be further improved. The K value of the N-vinyl lactam polymer (A) according to the Fikentscher method can be measured by the method described in the Examples.
[0026] The method for producing the N-vinyl lactam polymer (A) is not particularly limited, and the polymer can be produced by polymerizing monomer components. Specific examples, preferred examples and preferred ratios of the monomer components are as described above.
[0027] The method for initiating polymerization of the monomer components in the polymerization step is not particularly limited, and examples thereof include a method of adding a polymerization initiator, a method of irradiating with UV light, a method of applying heat, a method of irradiating with light in the presence of a photoinitiator, and the like. In the polymerization step, it is preferable to use a polymerization initiator when carrying out the polymerization. Examples of the polymerization initiator include peroxides such as hydrogen peroxide and t-butyl hydroperoxide; persulfates such as sodium persulfate, potassium persulfate and ammonium persulfate; dimethyl 2,2'-azobis(2-methylpropionate), 2,2'-azobis(isobutyronitrile), 2,2'-azobis(2-methylbutyronitrile), 2,2'-azobis(2-methylpropionamidine) dihydrochloride, 2,2'-azobis[N-(2-carboxyethyl)-2-methylpropionamidine] hydrate, 2,2'-azobis[2-(2-imidazolin-2-yl)propane], 2,2'-azobis[2-(2-imidazolin-2-yl)propane] dihydrochloride, 2,2'-azobis[2-(2-imidazolin-2-yl)propane] dihydrochloride, midazoline-2-yl)propane] disulfate hydrate, 2,2'-azobis(1-imino-1-pyrrolidino-2-methylpropane) dihydrochloride, 2,2'-azobis[N-(2-carboxyethyl)-2-methylpropionamidine]n hydrate, 2,2'-azobis[2-methyl-N-(2-hydroxyethyl)propionamide] and other azo compounds; benzoyl peroxide, lauroyl peroxide, peracetic acid, di-t-butyl peroxide, cumene hydroperoxide and other organic peroxides; and redox initiators that generate radicals by combining an oxidizing agent and a reducing agent, such as ascorbic acid and hydrogen peroxide, sodium sulfoxylate and t-butyl hydroperoxide, persulfate and metal salt, etc. Among these polymerization initiators, hydrogen peroxide, persulfate and azo compounds are preferred, and azo compounds are most preferred. Among them, 2,2'-azobis[2-(2-imidazolin-2-yl)propane]dihydrochloride, 2,2'-azobis[2-(2-imidazolin-2-yl)propane], 2,2'-azobis[2-(2-imidazolin-2-yl)propane]disulfate hydrate, 2,2'-azobis(2-methylpropionamidine)dihydrochloride, and 2,2'-azobis(2-methylbutyronitrile) are more preferred. These polymerization initiators may be used alone or in the form of a mixture of two or more kinds.
[0028] The amount of the polymerization initiator used is preferably 0.1 g or more and 10 g or less, more preferably 0.1 g or more and 7 g or less, and even more preferably 0.1 g or more and 5 g or less, per mole of the monomer used.
[0029] In the polymerization step, a chain transfer agent may be used as necessary. Specific examples of the chain transfer agent include thiol-based chain transfer agents such as mercaptoethanol and mercaptopropionic acid; halides such as carbon tetrachloride and methylene chloride; secondary alcohols such as isopropyl alcohol and glycerin; hypophosphorous acid (salts) such as hypophosphorous acid and sodium hypophosphite (including hydrates thereof); phosphorous acid (salts) such as phosphorous acid and sodium phosphite; sulfurous acid (salts) such as sodium sulfite; bisulfurous acid (salts) such as sodium hydrogen sulfite; dithionous acid (salts) such as sodium dithionite; pyrosulfurous acid (salts) such as potassium pyrosulfite, and hydrogen peroxide. The chain transfer agent is preferably hypophosphorous acid (salt), bisulfurous acid (salt), hydrogen peroxide, or mercaptopropionic acid, and more preferably hypophosphorous acid (salt). The chain transfer agent may be used alone or in the form of a mixture of two or more kinds. The amount of the chain transfer agent used is preferably 0 g or more and 20 g or less, and more preferably 0 g or more and 15 g or less, per mole of the amount of monomer (total monomers) used.
[0030] When a solvent is used in the polymerization step, the solvent is preferably an aqueous solvent, such as water, alcohols such as methyl alcohol, ethyl alcohol, isopropyl alcohol (2-propanol), n-butyl alcohol, and diethylene glycol, glycol, glycerin, and polyethylene glycol, and is preferably water. In order to improve the solubility of the monomer in the solvent, any suitable organic solvent may be added as necessary within a range that does not adversely affect the polymerization. Examples of such organic solvents include lower alcohols such as methanol, ethanol, and isopropyl alcohol; lower ketones such as acetone, methyl ethyl ketone, and diethyl ketone; ethers such as dimethyl ether, diethyl ether, and dioxane; and amides such as dimethylformaldehyde. These solvents may be used alone or in combination of two or more. The amount of the solvent used is preferably 40 to 300% by mass based on 100% by mass of the monomer.
[0031] In the above polymerization step, the polymerization temperature is not particularly limited, but is preferably from 20°C to 110°C, more preferably from 40°C to 105°C, and further preferably from 50°C to 105°C. The reaction time may be appropriately set depending on the reaction temperature, the types (properties), combinations, amounts used, etc. of the monomer components, polymerization initiator, and solvent so that the polymerization reaction is completed.
[0032] The method for producing the polymer preferably includes a step of aging the polymer after the polymerization reaction. By carrying out the aging step, the amount of residual monomers can be reduced. The temperature in the aging step is not particularly limited, but is preferably 50 to 105°C. The aging time in the aging step is not particularly limited, but is preferably 10 minutes to 5 hours, and more preferably 20 minutes to 3 hours.
[0033] In order to adjust the neutralization rate of the polymer to a suitable range, a neutralizing agent such as an alkali metal hydroxide, for example, sodium hydroxide may be added during or after the polymerization.
[0034] (Polyolefin resin (B)) The polyolefin resin (B) may be any polymer obtained by polymerizing a monomer component containing an olefin, and may be either a homopolymer or a copolymer. The olefin may be any hydrocarbon having a double bond, and examples thereof include linear or branched olefins having 2 to 20 carbon atoms, such as ethylene, propylene, 1-butene, 1-pentene, 1-hexene, 1-heptene, 1-octene, 1-decene, 1-dodecene, 1-tetradecene, 1-hexadecene, 1-octadecene, 1-eicosene, 3-methyl-1-butene, 3-methyl-1-pentene, 3-ethyl-1-pentene, 4-methyl-1-pentene, 4-methyl-1-hexene, 4,4-dimethyl-1-hexene, 4,4-dimethyl-1-pentene, 4-ethyl-1-hexene, 3-ethyl-1-hexene, butadiene, pentadiene, and hexadiene. The olefin preferably has 2 to 10 carbon atoms, more preferably 2 to 8 carbon atoms, further preferably 2 to 6 carbon atoms, and particularly preferably 2 to 4 carbon atoms. The olefin is preferably ethylene, propylene, 1-butene, 4-methyl-1-pentene, or 1-hexene, and more preferably ethylene or propylene.
[0035] The polyolefin resin (B) may have a structural unit derived from another monomer copolymerizable with an olefin. Specific examples of other monomers include alkyl (meth)acrylates such as methyl (meth)acrylate, unsaturated carboxylic acid monomers such as acrylic acid, unsaturated aromatic monomers such as styrene, acrylonitrile, and vinyl acetate.
[0036] The content of the olefin-derived structural units in the polyolefin resin (B) is not particularly limited, but is preferably 50 to 100 mass % relative to 100 mass % of all structural units, more preferably 65 to 100 mass %, even more preferably 80 to 100 mass %, and most preferably 100 mass %.
[0037] The content of structural units derived from monomers other than olefins in the polyolefin resin (B) is not particularly limited, but is preferably 0 to 50 mass% relative to 100 mass% of all structural units, more preferably 0 to 35 mass%, even more preferably 0 to 20 mass%, and most preferably 0 mass%.
[0038] The polyolefin resin (B) is preferably a homopolymer of ethylene, propylene, 1-butene, 4-methyl-1-pentene, 1-hexene, or the like, a copolymer of ethylene and propylene, or a copolymer of styrene, ethylene, and butylene, more preferably polyethylene, polypropylene, or a copolymer of ethylene and propylene, and even more preferably polypropylene.
[0039] (Hydrophilic modified polyolefin resin (C)) The hydrophilically modified polyolefin resin (C) is not particularly limited as long as it is a polyolefin modified with a compound having a hydrophilic group. The polyolefin resin used as the raw material for the hydrophilically modified polyolefin resin (C) may be a polymer obtained by polymerizing a monomer component containing an olefin, and specific examples and preferred forms are the same as those of the polyolefin resin (B) described above. The polyolefin resin used as the raw material for the hydrophilically modified polyolefin resin (C) may be the same as or different from the polyolefin resin (B) in the resin composition described above. The polyolefin resin constituting the hydrophilically modified polyolefin resin (C) is preferably polyethylene, polypropylene, a copolymer of ethylene and propylene, or a copolymer of styrene, ethylene and butylene, and more preferably polypropylene.
[0040] The compound having a hydrophilic group used for modifying the polyolefin resin is not particularly limited as long as it has a hydrophilic group and is capable of reacting with the polyolefin resin. Examples of the hydrophilic group include a carboxylic acid anhydride group, a carboxyl group, a sulfonic acid group, an amino group and salts thereof, a hydroxyl group, etc. Among these, preferred are acid groups such as a carboxylic acid anhydride group, a carboxyl group, a sulfonic acid group, and salts thereof, more preferred are a carboxylic acid anhydride group and a carboxyl group, and particularly preferred is a carboxylic acid anhydride group.
[0041] The compound used for modifying the polyolefin resin is preferably a compound having at least one hydrophilic group selected from the group consisting of a carboxylic anhydride group, a carboxyl group, a sulfonic acid group, an amino group, and salts thereof, and a hydroxyl group, which has the hydrophilic group and can react with the polyolefin resin, and is preferably a compound having an acid group and / or a salt thereof, and more preferably a compound containing a carboxylic anhydride group, or a compound having a carboxyl group or a salt thereof.
[0042] The ratio of hydrophilic groups in the hydrophilic modified polyolefin resin (C) is not particularly limited, but is preferably 0.01 to 20 mol% relative to 100 mol% of the structural unit (a) derived from the N-vinyllactam monomer (A1) in the N-vinyllactam polymer (A) described later. This allows the N-vinyllactam polymer (A) and the hydrophilic modified polyolefin resin (C) to interact more sufficiently, and the dispersibility of the N-vinyllactam polymer (A) in the resin composition can be further improved. The proportion of the hydrophilic group is more preferably 0.05 to 15 mol %, further preferably 0.1 to 10 mol %, and particularly preferably 0.2 to 5 mol %, relative to 100 mol % of the structural unit (a).
[0043] The hydrophilically modified polyolefin resin (C) preferably has a carboxylic anhydride group, a carboxyl group, or a salt group thereof, that is, the hydrophilically modified polyolefin resin (C) is preferably an acid-modified polyolefin resin. When the hydrophilically modified polyolefin resin (C) is an acid-modified polyolefin resin, the proportion of the acid groups is the same as the preferred proportion of the hydrophilic groups described above, but the acid value of the acid-modified polyolefin resin is preferably 3 to 300 mgKOH / g, more preferably 5 to 100 mgKOH / g, further preferably 7 to 70 mgKOH / g, and particularly preferably 10 to 60 mgKOH / g.
[0044] (Acid value of resin) The acid value (mgKOH / g) of the acid-modified polyolefin resin in the present invention is measured as follows. (1) Add xylene to the acid-modified polyolefin resin, heat to dissolve, and then titrate with a N / 10 methanolic solution of potassium hydroxide. (2) Determine the acid value using the following formula: Acid value (mgKOH / g)=(A×f×5.61) / S where A is the number of mL of 0.1 mol / L potassium hydroxide titration solution, f is the titer of 0.1 mol / L potassium hydroxide titration solution, and S is the amount of sample taken (g).
[0045] The weight average molecular weight of the hydrophilically modified polyolefin resin (C) is not particularly limited, but is preferably 5,000 to 2,000,000. More preferably, it is 10,000 to 500,000, even more preferably, it is 15,000 to 300,000, and particularly preferably, it is 20,000 to 200,000. When the weight average molecular weight of the hydrophilically modified polyolefin resin (C) is 5,000 or more, the strength of the resin composition tends to be further improved. In addition, when the weight average molecular weight of the hydrophilically modified polyolefin resin (C) is 2,000,000 or less, the dispersibility of the N-vinyl lactam polymer (A) tends to be further improved. The weight average molecular weight of the hydrophilically modified polyolefin resin (C) can be measured, for example, by gel permeation chromatography (GPC) under the following conditions. <Measurement of weight average molecular weight of hydrophilic modified polyolefin resin (C)> Equipment: Tosoh HLC-8321GPC / HT Detector: RI Column: Tosoh TSK-GEL GMHHR-H(20)HT x 3 Column temperature: 140℃ Flow rate: 1ml / min Calibration curve: Standard polystyrene Eluent: 1,2,4-trichlorobenzene
[0046] The method for producing the hydrophilically modified polyolefin resin (C) is not particularly limited as long as a hydrophilic group is bonded to the polyolefin resin. Examples of the method include a method of grafting a compound having a hydrophilic group (hereinafter also referred to as a hydrophilic group-containing compound) onto a polyolefin resin; a method of grafting a compound having a group that can become a hydrophilic group by hydrolysis or the like onto a polyolefin resin, followed by hydrolysis or the like; and a method of copolymerizing a part of the olefin constituting the polyolefin resin in the production of the polyolefin resin, by replacing with an unsaturated monomer having a hydrophilic group or an unsaturated monomer having a group that can become a hydrophilic group by hydrolysis or the like.
[0047] The method for grafting a compound having a hydrophilic group or a group that can become a hydrophilic group (hereinafter also referred to as a hydrophilic group-containing compound, etc.) to the polyolefin resin is not particularly limited. For example, the polyolefin resin can be obtained by a method in which a hydrophilic group-containing compound, etc. is reacted with a polyolefin resin in an organic solvent using a radical initiator, etc., or a method in which a polyolefin resin is reacted with a hydrophilic group-containing compound, etc. in the absence of a solvent using an extruder, a twin-screw kneader, etc. The reaction temperature between the polyolefin resin and the hydrophilic group-containing compound etc. is not particularly limited, but is preferably 50 to 300°C, more preferably 80 to 250°C, and further preferably 100 to 200°C.
[0048] The hydrophilic group-containing compound is not particularly limited as long as it reacts with the polyolefin resin, but is preferably a compound having a hydrophilic group and an ethylenically unsaturated hydrocarbon group. Examples of the compound having a hydrophilic group and an ethylenically unsaturated hydrocarbon group include unsaturated monocarboxylic acid monomers, unsaturated dicarboxylic acid monomers, sulfonic acid group-containing monomers, amino group-containing monomers, and hydroxyl group-containing monomers.
[0049] Examples of the unsaturated monocarboxylic acid monomer include acrylic acid, methacrylic acid, crotonic acid, tiglic acid, 3-methylcrotonic acid, 2-methyl-2-pentenoic acid, and salts thereof. Examples of the unsaturated dicarboxylic acid monomer include maleic acid, itaconic acid, mesaconic acid, citraconic acid, fumaric acid, salts thereof, and anhydrides thereof.
[0050] Examples of sulfonic acid group-containing monomers include 3-(meth)allyloxy-2-hydroxypropanesulfonic acid, 2-(meth)allyloxyethylenesulfonic acid, 2-acrylamido-2-methylpropanesulfonic acid, p-styrenesulfonic acid, α-methyl-p-styrenesulfonic acid, vinylsulfonic acid, vinylsulfamic acid, (meth)allyl sulfonic acid, isoprene sulfonic acid, 4-(allyloxy)benzenesulfonic acid, 1-methyl-2-propene-1-sulfonic acid, 1,1-dimethyl-2-propene-1-sulfonic acid, 3-butene-1-sulfonic acid, 1-butene-3-sulfonic acid, 2-acrylamido-1-methylpropanesulfonic acid, 2-acrylamidopropanesulfonic acid, 2-acrylamido-n-butanesulfonic acid, 2-acrylamido-2-phenylpropanesulfonic acid, 2-((meth)acryloyloxy)ethanesulfonic acid, and salts thereof.
[0051] Examples of the amino group-containing monomer include N,N-dialkylamino group-containing (meth)acrylates such as N,N-dimethylaminoethyl (meth)acrylate, N,N-diethylaminoethyl (meth)acrylate, N,N-dimethylaminopropyl (meth)acrylate, and N,N-diethylaminopropyl (meth)acrylate, as well as monomers obtained by adding a quaternizing agent to the above monomers or their neutralization with an acid such as hydrochloric acid or acetic acid; N,N-dimethylaminoethyl (meth)acrylamide, N,N-diethyl ... acrylamide, N,N-dimethylaminopropyl (meth)acrylamide, N,N-diethylaminopropyl (meth)acrylamide and other N,N-dialkylamino group-containing (meth)acrylamides, and monomers obtained by adding a quaternizing agent to the above monomers, or products neutralized with an acid such as hydrochloric acid; monomethylaminoethyl (meth)acrylate, monoethylaminoethyl (meth)acrylate, monomethylaminopropyl (meth)acrylate, monoethylaminopropyl (meth)acrylate, 2-(tert-butylamino)ethyl (meth)acrylate and other monoalkylamino group-containing (meth)acrylates, and products neutralized with an acid such as hydrochloric acid; monomethylaminoethyl (meth)acrylamide, monoethylaminoethyl (meth)acrylamide, monomethylaminopropyl (meth)acrylamide, monoethylaminopropyl (meth)acrylamide and other monoalkylamino group-containing (meth)acrylamides, and products neutralized with an acid such as hydrochloric acid; esters of (meth)acrylic acid and alkanolamines, such as 2-aminoethyl (meth)acrylate, and and their neutralization with an acid such as hydrochloric acid; N,N-diallylmethylamine and a monomer obtained by adding a quaternizing agent thereto, or a product neutralized with an acid such as hydrochloric acid; allylamine and a product neutralized with an acid such as hydrochloric acid; addition reaction products of unsaturated monomers having a cyclic ether-containing group having 2 to 8 carbon atoms, such as 1-allyloxy-3-dibutylamino-2-ol and 1-allyloxy-3-diethanolamino-2-ol, with an amine compound having 1 to 24 carbon atoms, and a monomer obtained by adding a quaternizing agent thereto, or a product neutralized with an acid such as hydrochloric acid.
[0052] Examples of hydroxyl group-containing monomers include hydroxyl group-containing (meth)acrylates such as α-hydroxymethyl acrylate, α-hydroxyethyl acrylate, 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, and 4-hydroxybutyl (meth)acrylate; unsaturated alcohols such as (meth)allyl alcohol and isoprenol; and alkylene oxide adducts in which alkylene oxide is added to the hydroxyl group of these alcohols.
[0053] Examples of compounds having a group that can become a hydrophilic group by hydrolysis or the like include esters of vinyl alcohol, such as vinyl acetate, and carboxylic acids; (meth)acrylamide, acetonitrile; glycidyl group-containing (meth)acrylates having 6 to 20 carbon atoms, such as glycidyl (meth)acrylate and β-methylglycidyl (meth)acrylate, alicyclic epoxy group-containing vinyl monomers having 6 to 20 carbon atoms, such as 4-vinyl-1,2-epoxycyclohexane and 5-vinyl-2,3-epoxynorbornane, and glycidyl group-containing acrylamides having 6 to 20 carbon atoms, such as N-(4-(2,3-epoxypropoxy)-3,5-dimethylphenylmethyl)acrylamide, and other epoxy group-containing monomers.
[0054] The compound having the hydrophilic group is preferably an unsaturated monocarboxylic acid monomer, an unsaturated dicarboxylic acid monomer, or a sulfonic acid group-containing monomer, more preferably an unsaturated monocarboxylic acid monomer, an unsaturated dicarboxylic acid monomer, even more preferably an unsaturated dicarboxylic acid monomer, and particularly preferably an anhydride of an unsaturated dicarboxylic acid.
[0055] In the method of copolymerizing a part of the olefin constituting the polyolefin-based resin by replacing it with an unsaturated monomer having a hydrophilic group or an unsaturated monomer having a group that can become a hydrophilic group by hydrolysis or the like, the unsaturated monomer having a hydrophilic group or the unsaturated monomer having a group that can become a hydrophilic group used is not particularly limited as long as it has a hydrophilic group or the like and can be copolymerized with the olefin, and examples thereof include the above-mentioned monomers to be grafted to the polyolefin-based resin.
[0056] (Other Ingredients) The resin composition of the present invention may contain other components in addition to the N-vinyl lactam polymer (A), the polyolefin resin (B) and the hydrophilically modified polyolefin resin (C). The other components are not particularly limited, but examples thereof include antioxidants, plasticizers, flame retardants, stabilizers, reinforcing materials, near-infrared absorbing agents, antistatic agents, colorants, fillers, and resin modifiers. The content of other components in the resin composition of the present invention is not particularly limited, but is preferably 0 to 3 mass % relative to 100 mass % of the resin composition of the present invention, and more preferably 0 to 1 mass %.
[0057] <Master batch> The present invention also relates to a masterbatch comprising an N-vinyllactam polymer (A) and a polyolefin resin and / or a hydrophilically modified polyolefin resin (C), in which the content of the N-vinyllactam polymer (A) is 20 to 150 mass% based on the total amount of the polyolefin resin (B) and the hydrophilically modified polyolefin resin (C). In this specification, the masterbatch means a concentrated mixture containing the N-vinyl lactam polymer (A) contained in the resin composition of the present invention at a high concentration. By using the masterbatch, the resin composition of the present invention and its molded article can be produced efficiently. The content of the N-vinyl lactam polymer (A) in the master batch is preferably 22 to 130% by mass, more preferably 25 to 120% by mass, based on the total amount of the polyolefin resin (B) and the hydrophilically modified polyolefin resin (C).
[0058] <Hydrophilic Agent> The present invention relates to a hydrophilizing agent comprising an N-vinyl lactam polymer (A), which is also a hydrophilizing agent used in a resin composition comprising a polyolefin resin (B) and a hydrophilically modified polyolefin resin (C). The content of the N-vinyl lactam polymer (A) in the hydrophilizing agent is not particularly limited, but is preferably 50 to 100% by mass, more preferably 80 to 100% by mass, relative to 100% by mass of the hydrophilizing agent.
[0059] The proportion of the polyolefin resin (B) in the resin composition in which the hydrophilizing agent is used is not particularly limited, but is preferably 45 to 99 mass % relative to 100 mass % of the resin composition, more preferably 60 to 98 mass %, and particularly preferably 70 to 95 mass %.
[0060] The proportion of the hydrophilically modified polyolefin resin (C) in the resin composition in which the hydrophilizing agent is used is not particularly limited, but is preferably 0.1 to 40 mass% relative to 100 mass% of the resin composition, more preferably 0.3 to 20 mass%, further preferably 0.5 to 10 mass%, and particularly preferably 0.8 to 5 mass%.
[0061] <Method of producing resin composition> The present invention is a method for producing a resin composition containing an N-vinyl lactam polymer (A), a polyolefin resin (B), and a hydrophilically modified polyolefin resin (C). The method includes a step (α) of mixing the N-vinyl lactam polymer (A) with the polyolefin resin (B) and / or the hydrophilically modified polyolefin resin (C). If either the polyolefin resin (B) or the hydrophilically modified polyolefin resin (C) is not mixed in the step (α), the method also includes a step (β) of mixing the mixture obtained in the step (α) with either the polyolefin resin (B) or the hydrophilically modified polyolefin resin (C) that was not mixed in the step (α).
[0062] In the method for producing the resin composition, specific examples and preferred forms of the N-vinyl lactam polymer (A), the polyolefin resin (B) and the hydrophilically modified polyolefin resin (C) are as described above.
[0063] The above-mentioned step (α) is not particularly limited as long as the N-vinyl lactam polymer (A) is mixed with the polyolefin resin (B) and / or the hydrophilically modified polyolefin resin (C). In the step (α), the N-vinyl lactam polymer (A) may be mixed with both the polyolefin resin (B) and the hydrophilically modified polyolefin resin (C), or only one of them may be mixed. In the above step (α), when the N-vinyl lactam polymer (A), the polyolefin resin (B), and the hydrophilically modified polyolefin resin (C) are mixed, the mixing time can be shortened. Furthermore, in the step (α), when either the polyolefin resin (B) or the hydrophilically modified polyolefin resin (C) is mixed with the N-vinyl lactam polymer (A), uneven mixing in the mixture can be sufficiently suppressed. In the above-mentioned method for producing a resin composition, in step (α), an N-vinyl lactam polymer (A) and a hydrophilically modified polyolefin resin (C) are mixed, and in step (β), the mixture obtained in step (α) is mixed with a polyolefin resin (B), which is one of the preferred embodiments of the present invention.
[0064] In the method for producing the resin composition, the proportions of the N-vinyl lactam polymer (A), the polyolefin resin (B) and the hydrophilically modified polyolefin resin (C) to be mixed are not particularly limited, but in step (α) or step (β), the amount of the polyolefin resin (B) used relative to 100% by mass of the N-vinyl lactam polymer (A) is preferably 250 to 10,000% by mass, more preferably 350 to 5,000% by mass.
[0065] In the above step (α) or step (β), the amount of the hydrophilically modified polyolefin resin (C) used relative to 100% by mass of the N-vinyl lactam polymer (A) is preferably 1 to 300% by mass, more preferably 2 to 100% by mass, and further preferably 3 to 50% by mass.
[0066] In the above step (α) or step (β), it is preferable to mix the hydrophilic polyolefin resin (C) so that the ratio of hydrophilic groups is 0.01 to 20 mol% relative to 100 mol% of the structural unit (a) derived from the N-vinyllactam monomer (A1) in the N-vinyllactam polymer (A). The ratio of hydrophilic groups is more preferably 0.05 to 15 mol%, even more preferably 0.1 to 10 mol%, and particularly preferably 0.2 to 5 mol% relative to 100 mol% of the structural unit (a).
[0067] The mixing temperature for the N-vinyl lactam polymer (A) in the above step (α) is not particularly limited, but is preferably 180 to 300° C. This allows the components to be mixed more thoroughly, more preferably 190 to 270° C., and even more preferably 200 to 250° C.
[0068] The mixing time for the N-vinyl lactam polymer (A) and the like in the above step (α) is preferably 1 to 180 minutes, more preferably 2 to 120 minutes, and further preferably 3 to 60 minutes. The apparatus used for the mixing in the above step (α) is not particularly limited, and examples thereof include kneading machines such as mixers, kneaders, kneading extruders, twin-screw extruders, and rolls.
[0069] In the method for producing the above resin composition, when performing step (β), the mixing temperature, mixing time, and apparatus are the same as those in step (α).
Examples
[0070] The present invention will be described in more detail with reference to the following examples, but the present invention is not limited to only these examples. Unless otherwise specified, "parts" means "parts by mass" and "%" means "% by mass".
[0071] <Measurement of weight-average molecular weight of N-vinyl lactam-based polymer (A)> The weight-average molecular weight was determined by measuring under the following conditions by gel permeation chromatography (GPC) method. Apparatus: HLC-8320GPC manufactured by Tosoh Corporation Detector: RI Column: TSK-GEL ALPHA-M, ALPHA-2500 manufactured by Tosoh Corporation Column temperature: 40 °C Flow rate: 0.8 ml / min Calibration curve: TSKgel standard Poly(ethylene oxide) Eluent: A solution obtained by mixing acetonitrile and 0.2 M aqueous sodium nitrate solution at a ratio of 1:4.
[0072] <Measurement of solid content> About 1 g of powder was weighed into a weighing can (mass W1 (g)) with a bottom diameter of about 5 cm (mass W2 (g)), and this was left standing in a constant-temperature dryer at 150 °C for 1 hour and dried. The total mass (W3 (g)) of the weighing can and the powder after drying was measured, and the solid content was determined from the following formula. Solid content (mass%) = [(W3 - W1) / W2] × 100
[0073] <K value> The K value of the polymer was calculated by preparing a 1% aqueous polymer solution in terms of solid content, measuring its viscosity at 25°C using a capillary viscometer (dilution type micro Ubbelohde viscometer I (K = 0.01)) manufactured by LA UDA, and applying the result to the following Fikentscher formula: K = (1.5logη rel -1) / (0.15+0.003c)+(300clogη rel +(c+1.5c log η rel ) 2 ) 1 / 2 / (0.15c+0.003c 2 ) Here, η rel is the relative viscosity (25°C) of the aqueous N-vinyllactam polymer solution to water measured by a capillary viscometer, and c is the concentration [mass%] of the N-vinyllactam polymer in the aqueous N-vinyllactam polymer solution.
[0074] <Dispersibility in polypropylene resin (AFM image evaluation)> A cross section was prepared using a microtome, and image processing was performed under the following measurement conditions to evaluate the surface irregularities. The width of the island structure was measured at three random points, and the average value was used to evaluate the surface irregularities. (Measurement conditions) Equipment: BRUKER Dimension Icon Measurement mode: Peak Force Tapping mode (Air) Probe: RTESPA-300 (spring constant = 40N / m) (Judgment criteria) ◎: The width of the island in the AFM elastic modulus image is less than 2 μm ○: The width of the island in the elastic modulus image of the AFM image is 2 μm or more and less than 4 μm ×: The width of the island in the elastic modulus image of the AFM image is 4 μm or more.
[0075] <Evaluation of hydrophilicity (contact angle of water)> The water contact angle of the unstretched film surface was measured using a contact angle measuring instrument (FACE contact angle meter CA-X model, manufactured by Kyowa Interface Science Co., Ltd.). (Judgment criteria) ◎: Water contact angle is less than 85° ○: Water contact angle is 85° or more and less than 90° ×: Water contact angle is 90° or more
[0076] <Resin strength evaluation> After molding the unstretched film, the film was judged to be damaged or not when peeled off from the release sheet. (Judgment criteria) ◎: Less than one film was damaged during the production of five films. Good: Two or more films but no more than three films were damaged during the production of five films. ×: Four or more films were damaged during the production of five films.
[0077] <Production Example 1> 373.9 parts by mass of ion-exchanged water, 9.0 parts by mass of 25% sodium hypophosphite monohydrate aqueous solution (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.), and 0.14 parts by mass of 48% by mass sodium hydroxide aqueous solution were charged into a SUS reaction vessel equipped with a Maxblend (registered trademark of Sumitomo Heavy Industries, Ltd.) type stirring blade, a glass lid, a stirring seal-attached stirrer, a nitrogen inlet tube, a reflux condenser, and a temperature sensor, and the solution in the reaction vessel was heated to 88 to 92 ° C. while stirring. Next, while maintaining the temperature at 90 ° C., 500 parts by mass of N-vinylpyrrolidone was added dropwise over 360 minutes, and 27.0 parts by mass of 10% by mass 2,2'-azobis(2-methylpropionamidine) dihydrochloride aqueous solution (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd., hereinafter referred to as "10% V-50") was added dropwise over 390 minutes through separate supply routes. The dropping of each component was carried out continuously at a constant dropping rate. Further, 8.5 parts by mass of an 88% by mass aqueous solution of formic acid was added 420 minutes after the start of polymerization, and 3.6 parts by mass of a 48% by mass aqueous solution of sodium hydroxide was added 480 minutes after the start of polymerization. After the addition of the 48% by mass aqueous solution of sodium hydroxide was completed, the temperature was maintained for another 60 minutes to perform aging, and a polymer composition was obtained. The obtained polymer composition was dried for 5 hours under reduced pressure conditions in a vacuum dryer (manufactured by Yamato Scientific Co., Ltd.: square vacuum constant temperature dryer DP33), and then the dried product was pulverized in a lab mill to obtain a powder containing polymer (1). The solid content of the obtained powder was 97.5%, the K value was 28, and the weight average molecular weight was 20,000. In addition, from the amount added and the solid content value of the obtained powder, the component amount of structural units derived from N-vinylpyrrolidone contained in the powder was calculated to be 8.55 mmol / g.
[0078] <Example 1> 15.0 parts by mass of the powder containing the polymer (1) obtained in Production Example 1, 83.3 parts by mass of a polypropylene resin (Sumitomo Noblen W101 manufactured by Sumitomo Chemical Co., Ltd.), and 1.7 parts by mass of an acid-modified polypropylene resin (UMEX 1001 manufactured by Sanyo Chemical Industries, Ltd., acid value: 26 mg KOH / g) were mixed in advance (i.e., 0.61 mol% of acid groups are contained relative to 100 mol% of structural units derived from N-vinylpyrrolidone) and kneaded for 5 minutes at 240 ° C. using a mixer (Labo Plastomill manufactured by Toyo Seiki Seisakusho Co., Ltd.) to obtain a resin composition (I-1). The obtained resin composition (I-1) was melt-press molded for 1 minute at 10 MPa using a manual heating press machine (IMC-180C manufactured by Imoto Seisakusho Co., Ltd.) to produce an unstretched film (I-2) having a thickness of 100 μm. The obtained resin composition (I-1) was observed by AFM to evaluate the dispersibility of the polymer (1). The average width of the island was 0.82 μm, so it was judged as "◎". The strength of the unstretched film (I-2) was evaluated from the viewpoint of whether the unstretched film (I-2) could be peeled off without damage when peeled off from the release sheet used during molding. In addition, the hydrophilicity of the obtained unstretched film (I-2) was evaluated by measuring the water contact angle. The results are summarized in Table 1.
[0079] <Example 2> 15.0 parts by mass of the powder containing the polymer (1) obtained in Production Example 1, 72.3 parts by mass of polypropylene resin (Sumitomo Noblen W101 manufactured by Sumitomo Chemical Co., Ltd.), and 12.7 parts by mass of acid-modified polypropylene resin (UMEX 1001 manufactured by Sanyo Chemical Industries, Ltd., acid value: 26 mg KOH / g) were mixed in advance (i.e., 4.59 mol% of acid groups are contained relative to 100 mol% of structural units derived from N-vinylpyrrolidone) and kneaded for 5 minutes at 240 ° C. using a mixer (Labo Plastomill manufactured by Toyo Seiki Seisakusho Co., Ltd.) to obtain a resin composition (II-1). The obtained resin composition (II-1) was melt-press molded for 1 minute at 10 MPa using a manual heating press machine (IMC-180C manufactured by Imoto Seisakusho Co., Ltd.) to produce an unstretched film (II-2) having a thickness of 100 μm. The same evaluation as in Example 1 was carried out, except that the obtained resin composition (II-1) and unstretched film (II-2) were used. The average of the island portions in the dispersibility evaluation was 0.46 μm, so it was judged as "◎". The results are summarized in Table 1.
[0080] <Example 3> 15.0 parts by mass of the powder containing the polymer (1) obtained in Production Example 1, 59.5 parts by mass of polypropylene resin (Sumitomo Noblen W101 manufactured by Sumitomo Chemical Co., Ltd.), and 25.5 parts by mass of acid-modified polypropylene resin (UMEX 1001 manufactured by Sanyo Chemical Industries, Ltd., acid value: 26 mg KOH / g) were mixed in advance (i.e., 9.21 mol% of acid groups are contained relative to 100 mol% of structural units derived from N-vinylpyrrolidone) and kneaded for 5 minutes at 240 ° C. using a mixer (Labo Plastomill manufactured by Toyo Seiki Seisakusho Co., Ltd.) to obtain a resin composition (III-1). The obtained resin composition (III-1) was melt-press molded for 1 minute at 10 MPa using a manual heating press machine (IMC-180C manufactured by Imoto Seisakusho Co., Ltd.) to produce an unstretched film (III-2) having a thickness of 100 μm. The same evaluation as in Example 1 was carried out, except that the obtained resin composition (III-1) and the unstretched film (III-2) were used. The average of the island portions in the dispersibility evaluation was 0.29 μm, so it was judged as "◎". The results are summarized in Table 1.
[0081] <Example 4> 3.0 parts by mass of the powder containing the polymer (1) obtained in Production Example 1, 91.9 parts by mass of a polypropylene resin (Sumitomo Noblen W101 manufactured by Sumitomo Chemical Co., Ltd.), and 5.1 parts by mass of an acid-modified polypropylene resin (UMEX 1001 manufactured by Sanyo Chemical Industries, Ltd., acid value: 26 mg KOH / g) were mixed in advance (i.e., 9.21 mol% of acid groups are contained relative to 100 mol% of structural units derived from N-vinylpyrrolidone) and kneaded for 5 minutes at 240 ° C. using a mixer (Labo Plastomill manufactured by Toyo Seiki Seisakusho Co., Ltd.) to obtain a resin composition (IV-1). The obtained resin composition (IV-1) was melt-press molded at 10 MPa for 1 minute using a manual heating press machine (IMC-180C manufactured by Imoto Seisakusho Co., Ltd.) to produce an unstretched film (IV-2) having a thickness of 100 μm. The same evaluation as in Example 1 was carried out, except that the obtained resin composition (IV-1) and unstretched film (IV-2) were used. The average of the island portions in the dispersibility evaluation was 0.26 μm, so it was judged as "◎". The results are summarized in Table 1.
[0082] <Example 5> 30.0 parts by mass of the powder containing the polymer (1) obtained in Production Example 1 and 25.4 parts by mass of an acid-modified polypropylene resin (UMEX 1001, manufactured by Sanyo Chemical Industries, Ltd., acid value: 26 mg KOH / g) were mixed in advance (i.e., 4.59 mol% of acid groups are contained relative to 100 mol% of structural units derived from N-vinylpyrrolidone). In this state, the mixture was kneaded for 5 minutes at 240 ° C. using a mixer (Labo Plasto Mill, manufactured by Toyo Seiki Seisakusho) to obtain a resin composition (V-1). Next, 27.7 parts by mass of the obtained resin composition (V-1) and 72.3 parts by mass of a polypropylene resin (Sumitomo Noblen W101, manufactured by Sumitomo Chemical Co., Ltd.) were kneaded for 5 minutes at 240 ° C. using a mixer (Labo Plasto Mill, manufactured by Toyo Seiki Seisakusho) to obtain a resin composition (V-2). The obtained resin composition (V-2) was melt-press molded at 10 MPa for 1 minute using a manual heating press (IMC-180C, manufactured by Imoto Manufacturing Co., Ltd.) to produce an unstretched film (V-3) having a thickness of 100 μm. The same evaluation as in Example 1 was carried out, except that the obtained resin composition (V-2) and unstretched film (V-3) were used. The average of the island portions in the dispersibility evaluation was 0.49 μm, so it was judged as "◎". The results are summarized in Table 1.
[0083] <Comparative Example 1> 15.0 parts by mass of the powder containing the polymer (1) obtained in Production Example 1 and 85.0 parts by mass of a polypropylene resin (Sumitomo Noblen W101 manufactured by Sumitomo Chemical Co., Ltd.) were mixed in advance and kneaded for 5 minutes at 240°C using a mixer (Labo Plastomill manufactured by Toyo Seiki Seisakusho Co., Ltd.) to obtain a resin composition (VI-1). The obtained resin composition (VI-1) was melt-press molded at 10 MPa for 1 minute using a manual heating press machine (IMC-180C manufactured by Imoto Seisakusho Co., Ltd.) to produce an unstretched film (VI-2) having a thickness of 100 μm. The same evaluation as in Example 1 was carried out except that the obtained resin composition (VI-1) and unstretched film (VI-2) were used. The average of the islands in the dispersibility evaluation was 4.9 μm, so it was judged as "X". The results are summarized in Table 1.
[0084] <Comparative Example 2> 15.0 parts by mass of the powder containing the polymer (1) obtained in Production Example 1 and 85.0 parts by mass of an acid-modified polypropylene resin (UMEX 1001 manufactured by Sanyo Chemical Industries, Ltd., acid value: 26 mg KOH / g) were mixed in advance (i.e., 30.70 mol% of acid groups are contained relative to 100 mol% of structural units derived from N-vinylpyrrolidone) and kneaded for 5 minutes at 240 ° C. using a mixer (Labo Plastomill manufactured by Toyo Seiki Seisakusho Co., Ltd.) to obtain a resin composition (VII-1). The obtained resin composition (VII-1) was melt-press molded at 10 MPa for 1 minute using a manual heating press machine (IMC-180C manufactured by Imoto Seisakusho Co., Ltd.) to produce an unstretched film (VII-2) having a thickness of 100 μm. The same evaluation as in Example 1 was carried out except that the obtained resin composition (VII-1) and unstretched film (VII-2) were used. The average of the islands in the dispersibility evaluation was 4.3 μm, so it was judged as "X". The results are summarized in Table 1.
[0085] <Comparative Example 3> 70.0 parts by mass of polypropylene resin (Sumitomo Noblen W101 manufactured by Sumitomo Chemical Co., Ltd.) and 30.0 parts by mass of acid-modified polypropylene resin (UMEX 1001 manufactured by Sanyo Chemical Industries, Ltd., acid value: 26 mg KOH / g) were mixed in advance and kneaded for 5 minutes at 240 ° C. using a mixer (Labo Plastomill manufactured by Toyo Seiki Seisakusho Co., Ltd.) to obtain a resin composition (VIII-1). The obtained resin composition (VIII-1) was melt-press molded at 10 MPa for 1 minute using a manual heating press machine (IMC-180C manufactured by Imoto Seisakusho Co., Ltd.) to produce an unstretched film (VIII-2) having a thickness of 100 μm. The unstretched film (VIII-2) obtained in Comparative Production Example 3 was subjected to the strength evaluation and hydrophilicity evaluation in the same manner as in Example 1. The results are summarized in Table 1.
[0086] [Table 1]
[0087] <Resin strength evaluation> Unstretched films (I-1, II-1, III-1) cut into pieces measuring 8cm x 4cm were held at both ends and slowly bent until the film broke. The film that was felt to be least likely to break (high strength) was given a score of 3, the film that was felt to be the next least likely to break was given a score of 2, and the film that was felt to be most likely to break (low strength) was given a score of 1. The evaluation was carried out by three people, and a resin strength evaluation (relative evaluation) was carried out on a scale of 1 to 9. The results are summarized in Table 2.
[0088] [Table 2]
[0089] From the above results, the strength of the resin tended to be better as the ratio of polypropylene resin was higher and the ratio of acid-modified polypropylene resin was lower.
Claims
1. A resin composition comprising an N-vinyl lactam polymer (A), a polyolefin resin (B), and a hydrophilically modified polyolefin resin (C).
2. The hydrophilic modified polyolefin resin (C) has at least one hydrophilic group selected from the group consisting of a carboxylic anhydride group, a carboxyl group, a sulfonic acid group, an amino group, salts thereof, and a hydroxyl group. The resin composition according to claim 1.
3. The resin composition according to claim 1 or 2, wherein the N-vinyl lactam polymer (A) has a structural unit (a) derived from an N-vinyl lactam monomer (A1), and the ratio of the hydrophilic group of the hydrophilically modified polyolefin resin (C) to 100 mol % of the structural unit (a) is 0.01 to 20 mol %.
4. The resin composition according to claim 1 or 2, wherein the content of the hydrophilically modified polyolefin resin (C) is 0.1 to 80 mass% relative to 100 mass% of the polyolefin resin (B).
5. 3. The resin composition according to claim 1, wherein the content of the N-vinyl lactam polymer (A) is 0.1 to 40% by mass relative to 100% by mass of the polyolefin resin (B).
6. The resin composition according to claim 1 or 2, wherein the polyolefin resin (B) is polypropylene.
7. The resin composition according to claim 1 or 2, wherein the polyolefin resin (B) constituting the hydrophilically modified polyolefin resin (C) is polypropylene.
8. 3. The resin composition according to claim 1, wherein the N-vinyl lactam polymer (A) has a structure derived from a phosphorus atom-containing compound.
9. The resin composition according to claim 1 or 2, wherein the N-vinyl lactam polymer (A) has a content of the structural unit (a) derived from the N-vinyl lactam monomer (A1) of 50 to 100 mol % relative to 100 mol % of all structural units.
10. The hydrophilically modified polyolefin resin (C) is an acid-modified polyolefin resin, 3. The resin composition according to claim 1, wherein the acid-modified polyolefin resin has an acid value of 3 to 300 mgKOH / g.
11. A hydrophilizing agent comprising an N-vinyl lactam polymer (A), The hydrophilizing agent is used in a resin composition containing a polyolefin resin (B) and a hydrophilically modified polyolefin resin (C).
12. A masterbatch comprising an N-vinyl lactam polymer (A), a polyolefin resin (B) and / or a hydrophilically modified polyolefin resin (C), The content of the N-vinyl lactam polymer (A) is 20 to 150 mass % based on the total amount of the polyolefin resin (B) and the hydrophilically modified polyolefin resin (C).
13. A method for producing a resin composition containing an N-vinyl lactam polymer (A), a polyolefin resin (B), and a hydrophilically modified polyolefin resin (C), comprising the steps of: The production method includes a step (α) of mixing an N-vinyl lactam polymer (A) with a polyolefin resin (B) and / or a hydrophilically modified polyolefin resin (C), When either the polyolefin resin (B) or the hydrophilically modified polyolefin resin (C) is not mixed in the step (α), the method for producing a resin composition includes a step (β) of mixing the mixture obtained in the step (α) with either the polyolefin resin (B) or the hydrophilically modified polyolefin resin (C) that was not mixed in the step (α).
Citation Information
Patent Citations
Thermoplastic resin composition
JP2002003731A
Polyolefin and polyvinylpyrrolidone blend
JP2021516710A